Variation of Type-B DNA X-Ray Fiber Diagrams with Base Composition - Bram, Stanley (1973)
Eight natural DNAs of widely differing base composition have been studied by x-ray diffraction in fibers at high relative humidity. The resulting type B diffraction diagrams showed that all of the DNAs had a 34-Å pitch and 3.4-Å interbase pair separation. However, the intensity distribution on the inner three layer lines was a strong function of the base content. In diffraction diagrams of very AT-rich DNA, the intensity of the first and third layer line was 2- or 3-times stronger than in the patterns of GC-rich DNA. These high humidity diffraction patterns agree with x-ray scattering from solutions of DNA. The results are interpreted to imply that each AT base pair may have a different cross section than a GC pair. If this is so, it would appreciably alter the currently held ideas concerning DNA recognition.